2006
DOI: 10.1007/11963516_30
|View full text |Cite
|
Sign up to set email alerts
|

Towards Probabilistic Model Checking on P Systems Using PRISM

Abstract: Abstract. In this paper it is presented the use of P systems and π-calculus to model interacting molecular entities and how they are translated into a probabilistic and symbolic model checker called PRISM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…17 Recently, it has been also applied to analysis of various biological systems, e.g. ERK/MAPK pathway, 4 FGF signalling pathway, 18 cell cycle in eukaryotes, 19 EGFR pathway, 20 T-cell receptor signaling pathway, 21 cell cycle control, 22 diabetes-cancer signaling network, 23 and genetic Boolean gates. 24,25 Two types of verification approaches are utilised in this paper, a qualitative analysis and a quantitative one.…”
Section: Model Checking Tools Allow Analysing Various Temporal Logic mentioning
confidence: 99%
“…17 Recently, it has been also applied to analysis of various biological systems, e.g. ERK/MAPK pathway, 4 FGF signalling pathway, 18 cell cycle in eukaryotes, 19 EGFR pathway, 20 T-cell receptor signaling pathway, 21 cell cycle control, 22 diabetes-cancer signaling network, 23 and genetic Boolean gates. 24,25 Two types of verification approaches are utilised in this paper, a qualitative analysis and a quantitative one.…”
Section: Model Checking Tools Allow Analysing Various Temporal Logic mentioning
confidence: 99%
“…Although techniques and data structures exist to minimise the model [14,16,13], in the majority of real applications (especially biological applications) the model remains intractable. Notable successes of standard and probabilistic model checking applied to simplified biological systems include [17,12,18,19]. In particular, in [17] the authors have shown the use of probabilistic model checking for the analysis of the cell cycle in eukaryotes, using a modelling language based on membrane systems and process algebra.…”
Section: Membrane Systems With Peripheral Proteinsmentioning
confidence: 99%
“…Notable successes of standard and probabilistic model checking applied to simplified biological systems include [17,12,18,19]. In particular, in [17] the authors have shown the use of probabilistic model checking for the analysis of the cell cycle in eukaryotes, using a modelling language based on membrane systems and process algebra. Platforms based on membrane systems including model checking have been previously implemented, [20].…”
Section: Membrane Systems With Peripheral Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRISM is used in [30] to model codon bias, studying a range of quantitative properties of the system. Finally, [31] uses PRISM, in combination with several other tools, to analyse gene expression modelled using P-Systems.…”
Section: Related Workmentioning
confidence: 99%